Law in everyday Japan : sex, sumo, suicide, and statutes - West, Mark D., 1968- (University of Chicago Press, 2005)
A compilation of case studies centred on seven everyday themes, from karaoke-based noise complaints to debt-induced suicide, this book offers a portrait of the way law intermingles with social norms, historically ingrained ideas, & cultural mores in Japan.